Organização política e resistência dos trabalhadores rurais em Santa Quitéria – Bacabeira/MA em face da implantação de grandes projetos de desenvolvimento na região - Filgueiras, Rayllanne Rebecca Pereira (2022)
This dissertation exposes the results of the research on the political organization and resistance of rural workers in the community of Santa Quitéria, in the municipality of Bacabeira/Maranhão. It analyzes the industrial development projects in Santa Quitéria, in the face of the implementation of large development projects in the region, highlights the implications of these projects in the lives of rural workers in Bacabeira, and analyzes the organization and resistance of these workers in the struggle for land. There is based on historical-dialectical materialism, with emphasis on historical and conceptual categories relevant to the object of study (organization, resistance, and class consciousness) and inserted in the theoretical-methodological framework used in the research carried out, for the purpose of dissertation. In this investigation process, diversified instruments and techniques were used, ranging from specialized literature to documentary analysis of news and data. To qualitatively understand the problem raised, bibliographic and documental research were adopted in terms of methodological procedures. In this way, this dissertation analyzes the logic behind the implementation, in the peripheral countries, of large-scale enterprises, highlighting the development policy in Brazil and its relationship of dependence with hegemonic countries in the process of capital expansion. It contextualizes conflicts and the struggle for land in Brazil, notably in Maranhão, as a historical issue, past and present of social classes. It also highlights the process of expansion of business projects financed by federal and transnational funds that announce the dynamization and modernization in the municipality of Bacabeira, place of implantation of the Premium I Refinery, and the particularity of the Santa Quitéria village and, mainly, its right to Earth. Finally, it analyzes the forms of expression of working-class consciousness in their organizations and political struggles, focusing the discussion on the organization and resistance of rural workers in Santa Quitéria and highlighting various tactics used by workers in the struggle for land as a historical and survival. In this context, it shows that the organization is a political process of resistance of the working class against the offensives of big capital